The Morita-Baylis-Hillman Reaction: Insights into Asymmetry and Reaction Mechanisms by Electrospray Ionization Mass Spectrometry - Verónica Carrasco-Sanchez (Molecules, 2009)
This short review presents new insights on the mechanism and online monitoring using electrospray ionization tandem mass spectrometry (ESI–MS/MS) of Morita–Baylis–Hillman (MBH) reactions. MBH reactions are versatile carbon-carbon organocatalyzed bond forming reactions, making them environmentally friendly due to general organocatalysts employed. The organocatalyst behavior, which controls the transition state and thus the enantioselectivities in the obtained products, is very important in the performance of asymmetric MBH transformations. Some recent techniques and advances in asymmetric transformations are reviwed, as well as online reaction monitoring and analysis of the reaction intermediates. The mechanism accepted nowadays is also review through the insights gained from the use of ESI–MS/MS techniques.